Making Kouchibouguac:: Acadians, the Creation of a National Park, and the Politics of Documentary Film during the 1970s - Rudin, Ronald (Acadiensis, 2010)
Abstract The documentary film Kouchibouguac, released by the Office national du film (ONF) in 1979, allowed Acadians – who had been removed from their lands to allow the creation of the national park of the same name – to tell their stories. This article explores the making of the film, with a particular focus upon the difficulties experienced by Acadians trying to find their voice within the Québécois-dominated ONF. It also reflects on the form of the film as well as the impact that it had within an Acadian population that was divided over the sporadically violent opposition to the park.